1997
DOI: 10.1007/s11606-006-5070-0
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Follow-up Testing After Curative Cancer Therapy: A Critical Review and Economic Analysis

Abstract: OBJECTIVE:To review (1) basic principles of follow-up in patients who are in complete remission following curative therapy for cancer; (2) evaluate the available data on followup strategies for testicular cancer, Hodgkin's disease, nonHodgkin's lymphoma, breast cancer, colorectal cancer, small cell and non-small cell lung cancer, and prostate cancer; and (3) analyze the cost of follow-up strategies METHODS: The English language literature was reviewed utilizing MEDLINE headings for the specific malignancies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 108 publications
(94 reference statements)
1
31
0
1
Order By: Relevance
“…Another suggestion was to use galium scanning for relapse detection. However, its utility in long-term follow-up remains to be established [4]. On the other hand, another long-term follow-up strategy is based mainly on clinical parameters and supported by studies [3,4] and recent recommendations [8].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another suggestion was to use galium scanning for relapse detection. However, its utility in long-term follow-up remains to be established [4]. On the other hand, another long-term follow-up strategy is based mainly on clinical parameters and supported by studies [3,4] and recent recommendations [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, its utility in long-term follow-up remains to be established [4]. On the other hand, another long-term follow-up strategy is based mainly on clinical parameters and supported by studies [3,4] and recent recommendations [8]. Weeks et al [3] found that the vast majority of relapses were detected at unscheduled visits for symptomatic disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations